Numerical modeling of phase change phenomena during Drop/Wall interaction in the context of thermal spraying - Boukhazani, Fathi; Rebhi, Redha; Didi, Faouzi; Elsayed, Ebrahim E.; Kezrane, Mohamed (Edelweiss Applied Science and Technology, 2025)
In the thermal spraying process studied, a molten aluminum particle is projected at high speed and flattens upon impact with a substrate. This phenomenon is modeled and simulated thermomechanically using the explicit software Abaqus. Using this method, the study considers the three forms of heat transfer, which account for a variable thermal contact conductance, and the particle’s and substrate’s thermomechanical properties are considered temperature-dependent. The proposed model is first validated against both experimental observations and previously published numerical findings. Careful monitoring of the droplets’ and substrate’s temperature variations is maintained throughout the impact process. The starting velocity of the droplet, the substrate’s temperature, and the substrate’s material qualities are some of the variables that affect the thickness of the solidified layer that forms when the molten droplet contacts the substrate. By incorporating the combined thermal and mechanical interactions between the impacting particle and the substrate, the model also provides valuable insights into the processes of heat transfer and lamellae creation in thermal spraying.